2015
DOI: 10.1002/btpr.2132
|View full text |Cite
|
Sign up to set email alerts
|

Flux balance analysis in the production of clavulanic acid byStreptomyces clavuligerus

Abstract: In this work, in silico flux balance analysis is used for predicting the metabolic behavior of Streptomyces clavuligerus during clavulanic acid production. To choose the best objective function for use in the analysis, three different optimization problems are evaluated inside the flux balance analysis formulation: (i) maximization of the specific growth rate, (ii) maximization of the ATP yield, and (iii) maximization of clavulanic acid production. Maximization of ATP yield showed the best predictions for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Intracellular ATP levels are normally regulated and maintained at a constant level by a robust cellular system. Indeed, in silico flux balance analysis of Streptomyces clavuligerus as a model organism indicates that the maximization of ATP yield is the best predictor of cellular behavior [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular ATP levels are normally regulated and maintained at a constant level by a robust cellular system. Indeed, in silico flux balance analysis of Streptomyces clavuligerus as a model organism indicates that the maximization of ATP yield is the best predictor of cellular behavior [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…FBA and metabolic flux analysis (MFA) [113], as well as convex network decomposition approaches such as elementary modes [114] and extreme pathways [115], model intracellular metabolism using the biochemical stoichiometry and other constraints such as thermodynamic feasibility [116,117] under pseudo steady state conditions. Constraint based approaches use linear programming [118] to predict productivity [111,119], yield [111], mutant behavior [120], and growth phenotypes [121] for biochemical networks of varying complexity, including genome scale networks. Constraint based models have also been used to identify strategies for the overproduction of desired compounds.…”
Section: Mathematical Modeling Of Cell Free Systemsmentioning
confidence: 99%
“…FBA studies have been previously used as a valuable tool for process design in antibiotic production, using maximization of cell growth as obfuncs [6,7,5]. Sánchez et al, [37] used CA production and ATP yield as obfuncs, as alternative functions to cell growth maximization [37]. In these simulations, using the experimental dataset from Bushell et al [19] as constraints, the maximization of ATP yield showed to be the best predictor of cellular behaviour [19].…”
Section: [Table 4]mentioning
confidence: 99%